How do you simplify this expression: (a^8a^6)^(1/7)/a^2?
2 Answers
1
Explanation:
Step 1) Combine the terms within the parenthesis using the rule for exponents:
Step 2) Simplify the numerator by using the rule for exponents:
Step 3)
We can use the rule from math:
Or, we can use the rule for exponents:
The answer is 1.
Explanation:
Here are some rules when working with exponents:
1. " "x^m xx x^n = x^(m+n)
2. " "x^m div x^n = x^(m-n)
3. " "(x^m)^n = x^(mn)
4. " "x^0 = 1
Now, to solve this question, it can be written as:
" "(a^8xxa^6)^(1/7) div a^2
=> (a^(8+6))^(1/7) div a^2
=> a^(14xx1/7) div a^2
=>a^2 div a^2 = a^(2-2) = a^0 = 1